2016
DOI: 10.1038/srep29761
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial ATP exocytosis: regulation of bladder compliance in the urine storage phase

Abstract: The bladder urothelium is more than just a barrier. When the bladder is distended, the urothelium functions as a sensor to initiate the voiding reflex, during which it releases ATP via multiple mechanisms. However, the mechanisms underlying this ATP release in response to the various stretch stimuli caused by bladder filling remain largely unknown. Therefore, the aim of this study was to elucidate these mechanisms. By comparing vesicular nucleotide transporter (VNUT)-deficient and wild-type male mice, we showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 61 publications
1
48
1
Order By: Relevance
“…VNUT is present in either insulin granules of β cells or glucagon granules of α cells [86,102], and glucose-responsive ATP secretion is lost [86]. As discussed later, ATP secretion from dorsal horn neurons and bladder epithelium in VNUT −/− mice also disappear [98,103]. Taken together, it can be concluded that VNUT −/− mice lose vesicular ATP release, and that VNUT is responsible for the vesicular storage and release of ATP.…”
Section: Wide Distribution Of Vnut-expressing Cellsmentioning
confidence: 67%
See 3 more Smart Citations
“…VNUT is present in either insulin granules of β cells or glucagon granules of α cells [86,102], and glucose-responsive ATP secretion is lost [86]. As discussed later, ATP secretion from dorsal horn neurons and bladder epithelium in VNUT −/− mice also disappear [98,103]. Taken together, it can be concluded that VNUT −/− mice lose vesicular ATP release, and that VNUT is responsible for the vesicular storage and release of ATP.…”
Section: Wide Distribution Of Vnut-expressing Cellsmentioning
confidence: 67%
“…Endogenous VNUT is colocalized with Lamp1, a lysosomal marker, in these cells [77], [81,92]. For details, see refs [4,81,86,92,93,96,98] but VNUT in astrocytes is not [75,76]. VNUT-mediated Δψ-driven ATP accumulation has been observed in living COS and HEK293 cells [78].…”
Section: Wide Distribution Of Vnut-expressing Cellsmentioning
confidence: 94%
See 2 more Smart Citations
“…Bladder extension is sensed by mechanosensor such as transient receptor potential cation channel subfamily V member 4 ( TRPV4) and Piezo1 via intracellular Ca 2+ influx [1618], which triggers ATP release from the bladder urothelium. Although many pathways are involved in the release of ATP, we identified the vesicular nucleotide transporter ( VNUT) , that mediates exocytosis [19] and conductive release connexin- or pannexin-hemichannels that mediate diffusible ATP release in the mucosa [2025], particularly Connexin26 ( Cx26 ) [26], as a main ATP release pathway in the bladder mucosa.…”
Section: Introductionmentioning
confidence: 99%